PERFORMANCE OF TOMATO UNDER PROTECTED CULTIVATION WITH DIFFERENT TRANSPLANTING TIME, PLANT SPACING AND TRAINING SYSTEM - SHILPA KAUSHAL; SHUBHAM (The Journal of Research ANGRAU, 2025)
Cultivation shift towards the cash crops becomes a major thrust area for generating higher  incomes but the approach requires scientific attention. Therefore, a study was conducted during  2021-22 and 2022-23 to access the effect of different transplantation time, spacing and training  system on soil nutrients status and growth of tomato. The results showed that early transplanting  on 15th March, with a spacing of 75 cm × 30 cm and training the plants to two shoots, led to the  highest fruit length and breadth, indicating a significant improvement in fruit development under  these conditions. Similar treatment combinations resulted in the highest values across various  yield parameters. These included fruits per cluster at 5.0, 4.6, and 4.5; fruits per plant at 26.8,  25.1, and 25.7; average fruit weight of 75.6 g, 71.5 g, and 79.9 g; and fruit yield per plant of 2.04 kg, 1.81 kg, and 1.75 kg. In another observation, similar treatments achieved fruits per cluster of 5.3, 5.0, and 5.0; fruits per plant of 32.0, 28.9, and 28.5; fruit weights of 76.8 g, 72.9 g, and 71.8  g; and fruit yields per plant of 2.22 kg, 1.91 kg, and 1.89 kg. Additionally, the maximum fruit yield  per 100 m² was registered with 1007.5 kg and 1100 kg, and thus, highlighting the effectiveness of  these treatment combinations in enhancing fruit productivity. However, plants spaced at 60 cm  ×30 cm attained maximum yield which was 10.6-14.4% higher over 75 cm ×30 cm. No significant difference was found on soil available nutrient content. Study identified the treatment combination  of early transplanting along with wider planting with 75 cm ×30 cm and two shoots training as an  eminent approach for growing tomato hybrids under poly house.